2007
DOI: 10.1007/s10967-007-0202-5
|View full text |Cite
|
Sign up to set email alerts
|

The problem of large samples: An activation analysis study of electronic waste material

Abstract: Large-volume instrumental photon activation analysis (IPAA) was used for the investigation of shredded electronic waste material. Sample masses from 1 to 150 grams were analyzed to obtain an estimate of the minimum sample size to be taken to achieve a representativeness of the results which is satisfactory for a defined investigation task. Furthermore, the influence of irradiation and measurement parameters upon the quality of the analytical results were studied. Finally, the analytical data obtained from IPAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Similar problems exist with collection and recycling in advanced economies such as Japan, Korea and the European Union (Tong & Wang, 2004;Li et al, 2006;Liu et al, 2006a;Liu et al, 2006b;Terazono, et al, 2006, Oguchi et al, 2008Lee et al, 2007;Huisman et al, 2007;Selin and VanDeveer, 2006;Hageluken, 2006a;. Between the years 1999 to 2002, the amount of WEEE in the EU went from 1 megaton to over 6 megatons (Segebade et al, 2007). It is estimated that 80°/o of the world's computer e-waste is exported to Asia and that 90°/o of these exports were illegal, under the guise of "recycling" (Bi et al, 2007).…”
Section: Electronic Waste In the Developed Worldmentioning
confidence: 91%
See 1 more Smart Citation
“…Similar problems exist with collection and recycling in advanced economies such as Japan, Korea and the European Union (Tong & Wang, 2004;Li et al, 2006;Liu et al, 2006a;Liu et al, 2006b;Terazono, et al, 2006, Oguchi et al, 2008Lee et al, 2007;Huisman et al, 2007;Selin and VanDeveer, 2006;Hageluken, 2006a;. Between the years 1999 to 2002, the amount of WEEE in the EU went from 1 megaton to over 6 megatons (Segebade et al, 2007). It is estimated that 80°/o of the world's computer e-waste is exported to Asia and that 90°/o of these exports were illegal, under the guise of "recycling" (Bi et al, 2007).…”
Section: Electronic Waste In the Developed Worldmentioning
confidence: 91%
“…A substantial increase in domestic participation is implicit in the proper control and management of the WEEE problem. Product design, including full-cycle "cradle-tograve" design, as well as the advancement of recycling technologies and processes, are all emphasized as important in achieving proper domestic management of WEEE (Meech, 2006;Hammond & Beullens, 2007;Bakar & Rahimifard, 2007;Kongar & Gupta, 2006;Kopacek & Kopacek, 2006;Segebade et al, 2007;Lofthouse, 2007;Schlummer et al, 2006;Ahluwalia & Nema, 2006). Nevertheless, despite advancement in these areas, systematic improvements in OECD countries must be made to address the domestic WEEE problem and bring about responsible recycling practices.…”
Section: Electronic Waste In the Developed Worldmentioning
confidence: 99%
“…LSNAA to study irregular shape and size nuclear cladding materials of zircaloys, stainless steels and aluminum as well as large size synthetic solid and liquid samples [31][32][33]. Activation analysis studies of large volume electronic waste material and municipal solid waste have been reported by Segebade et al [34] and Haddad and Alsomel [15] respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Concepts that are widely applied in developed countries for waste treatment may not be suitable in the less developed countries. Thermogravimetric analysis (Kowalska et al, 2006) and large-volume instrumental photon activation analysis (IPAA) (Segebade et al, 2007) are analytical tools to design the e-waste management strategy. Non-metals separated from pulverised waste printed circuit boards (PCBs) were reused as a new modifier to improve the performance of asphalt (Guo et al, 2009).…”
Section: E-waste Managementmentioning
confidence: 99%